1970
DOI: 10.3126/on.v8i1.4328
|View full text |Cite
|
Sign up to set email alerts
|

Limnological Studies Related to Physico-Chemical Characteristics of Water of Santragachi and Joypur Jheel, W.B., India

Abstract: The present study deals with the seasonal limnological investigation related to physico-chemical characteristics of water of the Santragachi and Joypur Jheel, West Bengal, India. Besides temperature and meteorological data, 17 limnological parameters were tested following standard methods at 3 sampling sites/stations of each Jheel. The physico-chemical parameters (transparency, pH, DO, BOD, COD, free CO2, total alkalinity, conductivity, CaCO3, TSS, TDS, Chloride, Ammonia, Nitrite, Nitrate, Phosphate, etc.) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Free CO2 content in water increases with increase in temperature (Agrawal 1999). Maximum free CO2 during summer may be due to decomposition of organic matter by microbes at the bottom (Patra et al 2010). The mean value of hardness was recorded higher in the wet season (314.6 ±18.69 mg dm -3 ) than in the dry season (218 ±8 mg dm -3 ).…”
Section: Physical and Chemical Parametersmentioning
confidence: 89%
“…Free CO2 content in water increases with increase in temperature (Agrawal 1999). Maximum free CO2 during summer may be due to decomposition of organic matter by microbes at the bottom (Patra et al 2010). The mean value of hardness was recorded higher in the wet season (314.6 ±18.69 mg dm -3 ) than in the dry season (218 ±8 mg dm -3 ).…”
Section: Physical and Chemical Parametersmentioning
confidence: 89%
“…Several studies on local and migratory water-bird population and the effects of bird aggregation on the physicochemical conditions of lake water and vice versa have been conducted in the state West Bengal of India by many workers (Patra et al 2010;Datta, 2011;Singha Roy et al 2011 andBhattacharya and Roy, 2013). A few research works have been carried out in Purbasthali bird sanctuary concerning the ecology, environmental threat and socioeconomic issues (Ganesan and Khan, 2007;Ganguly, 2015;Biswas Roy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The rich vegetation layers and stable community structure increase the spatial heterogeneity and improve the vegetation biomass in this area, providing birds with complex survival opportunities for foraging, nesting, and avoiding natural enemies (McCain, 2009). Birds' preference for wetlands is influenced by a complex of characteristics such as water chemistry, aquatic vegetation, and physical features (Patra et al, 2011). The study showed that the inorganic nitrogen, reactive phosphate and suspended solids in the water of the Yingwuzhou wetland were reduced after purification from Habitat Pattern A into Habitat Pattern B (Chen et al, 2020) which might also lead birds to choose Habitat Pattern B with better water quality as their habitat.…”
Section: Coastal Restoration Projects Provide Good Habitat For Birds ...mentioning
confidence: 99%